MONGOLIAN TRIBAL NAMES IN THE HISTORIA TARTARORUM - Uhrin Dorottya (Acta Mongolica, 2013)
This essay aims to introduce and analyse a less known source called Historia Tartarorum (in English Tartar Relation) written by C. de Bridia, a fransiscan friar, in July 1247. This text based on Carpini’s work and because of it in the translations Bridia’s own work was written by cursive.